Morphometric diversity and phenotypic relationship among indigenous buffaloes of Banten, Indonesia - Dewi Murni; UMIE LESTARI; SRI ENDAH INDRIWATI; ACHMAD EFENDI; NANI MARYANI; MOHAMAD AMIN (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Murni D, Lestari U, Indriwati SE, Efendi A, Maryani N, Amin M. 2020. Morphometric diversity and phenotypic relationship among indigenous buffaloes of Banten, Indonesia. Biodiversitas 21: 933-940. This study aimed to describe the morphometric diversity and phenotypic relationship among indigenous buffaloes of Banten, Indonesia. In this study, 125 buffaloes from six regions were investigated based on 11 morphometric characters. Morphometric diversity was analyzed using multivariate discriminant analysis. The Euclidean genetic distances were used to estimate the phenotypic relationship among the buffalo populations. The indigenous buffaloes of Banten have high morphometric diversity, with a coefficient from 2.83 to 41.43%. The body length and chest circumference can be used as a morphometric marker to determine potential indigenous buffaloes as their high correlation coefficient value (0.506). The Serang district buffaloes have the highest mean of body length and chest circumference, which shows that this population is potential compared to the populations from other regions. The morphometric of buffalo population from Serang City, Cilegon City, Serang District, and Pandeglang District tend to be homogenous. Meanwhile, Lebak and Tangerang District population tends to heterogeneous. According to Euclidean distance analysis, the proximate phenotypic relationship was between Serang and Pandeglang District's buffalo populations. Our results indicated that morphometric diversity and phenotypic relationships of the populations were related to geographical origins and can be used to determine the potential indigenous of buffaloes.